Progress towards an OMERACT-ILAR guideline for economic evaluations in rheumatology. Issue 4 (1st April 2002) - Gabriel, S E; Tugwell, P; Drummond, M
Abstract : A working report from the OMERACT Health Economics Group. The group is working towards creating common standards for economic evaluation in rheumatology and also towards improving the scientific underpinning of economic evaluation, particularly pertaining to the rheumatic diseases. Preliminary recommendations for "reference cases" in osteoporosis, rheumatoid arthritis, and osteoarthritis are proposed.